1999
DOI: 10.1074/jbc.274.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Changes in GroEL/Gp31 Affinity as a Mechanism for Allele-specific Genetic Interaction

Abstract: Previous work has shown that the GroEL-GroES interaction is primarily mediated by the GroES mobile loop. In bacteriophage T4 infection, GroES is substituted by the gene 31-encoded cochaperonin, Gp31. Using a genetic selection scheme, we have identified a new set of mutations in gene 31 that affect interaction with GroEL; all mutations result in changes in the mobile loop of Gp31. Biochemical analyses reveal that the mobile loop mutations alter the affinity between Gp31 and GroEL, most likely by modulating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 44 publications
(61 reference statements)
1
43
0
Order By: Relevance
“…The increase in affinity was explained as being a result of decreasing the disorder of the mobile loop or, conversely, preordering the binding structure of the mobile loop. Likewise, changes in GroEL-GroES binding affinity of the bacteriophage T4 co-chaperonin were shown to be controlled by amino acid preferences for ␤-sheet, which modulate the formation of a GroEL binding ␤-hairpin conformation (16). Therefore, an understanding of the structure and folding of the mobile loop is essential to understanding the functional interaction between co-chaperonins and chaperonins.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in affinity was explained as being a result of decreasing the disorder of the mobile loop or, conversely, preordering the binding structure of the mobile loop. Likewise, changes in GroEL-GroES binding affinity of the bacteriophage T4 co-chaperonin were shown to be controlled by amino acid preferences for ␤-sheet, which modulate the formation of a GroEL binding ␤-hairpin conformation (16). Therefore, an understanding of the structure and folding of the mobile loop is essential to understanding the functional interaction between co-chaperonins and chaperonins.…”
mentioning
confidence: 99%
“…Therefore, the folding of at least 16 residues is coupled to the binding of 3 residues to GroEL. A multitude of mutations in the mobile loops of GroES and other co-chaperonins is known to affect function (11,(13)(14)(15)(16)(17)(18)(19)(20). Since many of these mutations occur away from residues directly involved in forming the binding interface, we have hypothesized that the mutations affect the folding transition (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations encoding substitutions throughout the GroES and Hsp10 mobile loops have been identified that alter affinity by affecting the flexibility of the mobile loop (33)(34)(35)(36)(37). Mutants that allow better binding are probably sequence alterations that disfavor mobility, while mutants that weaken binding either increase the entropy, and therefore flexibility of the mobile loop, or promote an incorrect mobile loop conformation (32).…”
mentioning
confidence: 99%
“…It took a few more years to demonstrate directly that Gp31 is a bona fide GroEL co-chaperone (van der Vies et al 1994;Richardson et al 1999). Further studies showed that many large bacteriophage encode Gp31-like proteins capable of substituting for GroES in E. coli growth (reviewed in Ang et al 2000Ang et al , 2001Keppel et al 2002).…”
Section: Host-and Phage-encoded Groel Co-chaperonesmentioning
confidence: 99%